1996
DOI: 10.1093/infdis/173.2.340
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with Envelope Subunit Vaccine Products Elicits Neutralizing Antibodies against Laboratory-Adapted but Not Primary Isolates of Human Immunodeficiency Virus Type 1

Abstract: Phase I studies of volunteers not infected with human immunodeficiency virus type 1 (HIV-1) have shown that immunization with envelope subunit vaccine products elicits antibodies that neutralize laboratory-adapted (prototype) HIV-1 strains in vitro. Prototype strains are adapted to grow in continuous (neoplastic) cell lines and are more susceptible to neutralization than are primary isolates cultured in human peripheral blood mononuclear cells. In this study, 50 sera from nine phase I vaccine trials and 16 fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
252
1
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 414 publications
(260 citation statements)
references
References 54 publications
5
252
1
2
Order By: Relevance
“…Early efforts in HIV vaccine development focused on the induction of humoral responses by using recombinant Env glycoproteins [2][3][4][5]. The immunogenicity of recombinant Env protein-based vaccines was poor in humans, as shown by overall low-level binding antibodies measured by solid phase assays [6] and by the narrow spectrum of neutralizing activities mainly against T-cell line adapted (TCLA) viral isolates [7][8][9]. Ultimately, recombinant protein-based HIV-1 vaccines failed to show protection efficacy in Phase III clinical trials [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Early efforts in HIV vaccine development focused on the induction of humoral responses by using recombinant Env glycoproteins [2][3][4][5]. The immunogenicity of recombinant Env protein-based vaccines was poor in humans, as shown by overall low-level binding antibodies measured by solid phase assays [6] and by the narrow spectrum of neutralizing activities mainly against T-cell line adapted (TCLA) viral isolates [7][8][9]. Ultimately, recombinant protein-based HIV-1 vaccines failed to show protection efficacy in Phase III clinical trials [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…No subject was vaccinated during the protocol, and the immune response changes were documented before any subject changed antiretroviral therapy. Finally, serum from patients was analyzed for neutralizing antibodies to laboratory HIV strains and to autologous viral isolates (19). No subjects developed neutralizing antibodies to env.…”
Section: Resultsmentioning
confidence: 99%
“…One explanation for the discordance between ADCVI activity and the other Abs is our use of a clinical R5 strain of HIV-1 grown in PBMCs (46). Additionally, we and others (13,30,31) have shown that functional Ab responses directed against infected cells and requiring Fc-Fc␥R interactions do not necessarily correlate with neutralizing or binding Ab levels; our current results further underscore the fact that Ab functions are not necessarily predictable from binding assays and that assays used to measure one function might not predict another.…”
Section: Discussionmentioning
confidence: 99%